Optimizing Mushroom Spawn Production In Uganda - Malakar, Pradeep; Tan, Qi; Chen, Mingjie; Xing, Zengtao; Buswell, John; Sun, Qui; Wei, Mr Xiaoping; Kwesiga, Charles; Tugume, Arthur; Byandusya, Peace; Verfaillie, Magda; Mayambala, Janiffer; et al. (ICAR-Directorate of Mushroom Research., 2014)
Most farmers in Uganda own less than an acre of land, which is typically used to grow crops such as bananas, pineapples and cassava. Mushroom cultivation requires less space, takes place near the home and has the potential to improve the lives of thousands of small land holders, especially women. However, for various reasons, farmer groups in Uganda are presently unable to meet the demand for high quality, fresh and dried mushrooms. This project, initiated in March 2014 and funded through the AgriTT (Agricultural Technology Transfer) programme, is directed at addressing current deficiencies in, and impediments to, the development of the Ugandan mushroom industry. The project introduced several key innovations that have made China the world’s pre-eminent mushroom producer. These include: the provision of uninterrupted supplies of robust, high quality, genetically-stable spawn (through the Mushroom Training and Resource Centre [MTRC] and registered spawn producers) capable of generating high yields of quality mushrooms and using a wide range of cheap, readily-available cultivation substrates under the diverse climatic conditions prevailing in different regions of Uganda. It also includes establishing a germplasm bank to protect and conserve indigenous mushroom resources and a comprehensive breeding programme for enhanced strain performance. In addition, it incorporates research, educational and training elements involving MTRC, the Uganda Industrial Research Institute, Makerere University and Guizhou Academy of Agricultural Sciences, and a Field Technical Service to serve as a conduit to facilitate feedback from the growers based on their practical experiences as well as technology transfer between farmers and researchers. The programme will ensure a sustained supply of ‘home-grown’ mushrooms and well-trained mushroom biologists, and expedite engagement with the Ugandan government aimed at establishing a National Mushroom Policy and Strategy.